DECONVOLUTION METHOD TO OBTAIN COMPOSITION PROFILES FROM SEM BACKSCATTERED ELECTRON SIGNAL PROFILES FOR BULK SPECIMENS - Konkol, A; Wilshaw, P; Booker, G (Elsevier, 1994)
Compositional profiles across CdTe/Cd(y)Hg(1-y)Te interfaces in bulk specimens have been determined from backscattered electron (BSE) atomic-number contrast line profiles obtained using the scanning electron microscope. To improve the spatial resolution in the interface region, a numerical deconvolution method has been developed which enables the distorting effects associated with the beam size, the specimen scattering effects and the detector characteristics to be substantially removed from the BSE profile. The effectiveness of the method is demonstrated by reproducing closely the same compositional profile for individual specimens from BSE profiles obtained at different beam energies. The deconvolution method improved the resolution from ~100 to ~20 nm.